Evaluation of the Free Nutritional Meal Program (MBG) Policy in Indonesia Based on William N. Dunn's Perspective - Wilyus Martin Baran Cia; Muhammad Hamdani; M Yunus Adi putra (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
The Free Nutritious Meal (MBG) program stands as a strategic policy breakthrough by the Indonesian Government, serving as a foundation for human resource development toward the Golden Indonesia 2045 vision. This study conducts a critical analysis of the MBG policy by adopting William N. Dunn’s evaluation framework, which encompasses six fundamental dimensions: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Through a literature review approach, the research identifies a contradictory policy performance. Regarding effectiveness, while the program has proven successful in stimulating student attendance and classroom concentration, these achievements are overshadowed by systemic failures in food safety, which triggered 211 mass poisoning incidents across various provinces. From an efficiency perspective, the MBG funding structure is considered problematic as it relies on significant budget reallocations from primary education and health sectors. Furthermore, in terms of adequacy and appropriateness, the program design is deemed to have not yet addressed the root causes of stunting because interventions are only conducted at school age, thereby missing the critical momentum of the first 1,000 Days of Life (HPK). Disparities in the equity criterion are also evident in the regressive distribution of benefits and the fact that 89% of operational kitchens lack hygiene and sanitation certification. Meanwhile, bureaucratic responsiveness is observed to be largely reactive, taking action only after public health crises emerge in the field. This study concludes that the MBG program is currently trapped in administrative and logistical achievements, necessitating an urgent and comprehensive policy evaluation.